2014
DOI: 10.1016/j.jot.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in coatings for magnesium-based stents and orthopaedic implants

Abstract: Magnesium (Mg)-based biodegradable materials are promising candidates for the new generation of implantable medical devices, particularly cardiovascular stents and orthopaedic implants. Mg-based cardiovascular stents represent the most innovative stent technology to date. However, these products still do not fully meet clinical requirements with regards to fast degradation rates, late restenosis, and thrombosis. Thus various surface coatings have been introduced to protect Mg-based stents from rapid corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 160 publications
(153 reference statements)
0
25
0
Order By: Relevance
“…Among them, Mg-based alloys have been widely explored in stent applications because of their biodegradability, bioabsorbility, and low thrombogenicity1234. However, the main drawbacks of conventional Mg alloys are insufficient mechanical strength and rapid corrosion accompanied with hydrogen gas evolution, pH increase, and premature loss of mechanical integrity5.…”
mentioning
confidence: 99%
“…Among them, Mg-based alloys have been widely explored in stent applications because of their biodegradability, bioabsorbility, and low thrombogenicity1234. However, the main drawbacks of conventional Mg alloys are insufficient mechanical strength and rapid corrosion accompanied with hydrogen gas evolution, pH increase, and premature loss of mechanical integrity5.…”
mentioning
confidence: 99%
“…Sustained drug release is essential in preventing an inflammation response and reducing late restenosis. It has been shown that porosity and size had effects on the drug release mechanisms of PLGA [52]. Nano porosities in coating layers facilitate the mechanical interlocking of the cells with the surface, thereby favouring osseointegration process.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2) in the review by Ma et al [34], the subject is coatings for both Mg-based bioresorbable stents and orthopaedic implants and only a minimal reference to corrosion is made; and 3) the review by Uddin et al [35] focused on surface treatments for controlling the corrosion of Mg and Mg-based alloys for applications in orthopaedics and cardiovascular stenting; and 4) the review by Hornberger et al [36] is on coatings for biomedical applications and not on stents per se and the coverage on corrosion is short.…”
Section: Introductionmentioning
confidence: 99%